THE IMPACT OF VOCABULARY DEPTH AND BREADTH TO THE TOEFL READING SUBTEST IN IAIN KEDIRI - Anam, Moh Khoirul (Universitas Negeri Makassar, 2019)
TOEFL has been provided as a standardized test to measure the English proficiency of non-native speakers. However, one thing should be considered that TOEFL is still a big challenge for non-native English learners, especially for EFL learners. This is one of the factors, related to how proficient the vocabulary knowledge which students have. Therefore, this study aimed to investigate to what extent the relation between vocabulary knowledge, breadth and depth, and TOEFL test, especially reading subtest session. Participants of this study were undergraduate English students who never took a TOEFL preparation course. To help analyze data, IBM SPSS 24 version with Spearman rank correlation analysis was used to make it more precise. The result of Spearman rank correlation analysis revealed that there was a significant correlation among the variables. This result supports some previous studies focusing on the same topic.